Physical property differences of source rocks in the Lucaogou Formation and adsorption ability variation under their influence - Ge, Dongfeng; Lv, Dawei; Yao, Peng; Wen, Shupeng; Li, Jiahui; Lei, Guoming (Frontiers in Earth Science, 2023)
In this paper, Quanzijie shale gas collected from the southern margin of Junggar Basin is taken as a study area, shale gas resources are investigated and evaluated using organic-rich shale section. On this basis, the investigation and evaluation of shale gas resources in Lucaogou Formation are studied. Reservoir performance, preservation conditions, compressibility and gas bearing property of gas bearing shale intervals are identified. The results are as follows. Vertical and horizontal lithological and lithofacies variation of source rocks of Lucaogou Formation are clarified. This layer is characterized by upward thinning of grain size and upward darkening of color in vertical direction. The layer can be divided into upper and middle-lower section, that is, organic shale in the upper section is most developed, and sandstone and dolomite in the middle and lower area are more developed. Main hydrocarbon source rocks are developed in the upper area of Lucaogou Formation. Total thickness of the hydrocarbon source rocks is 78.12 513.73m. The lithology is mainly gray black shale, silty mudstone, and oil shale. The average organic carbon content is 4.86%. The maturity of organic matter is mainly 0.7 0.8%. Shale reservoir has a high content of brittle minerals, but the physical properties of both shale and sandstone reservoirs are poor. It is generally an ultra-low porosity and ultra-low permeability reservoir, in which the oil and gas reservoir space is mainly fractures.